Protection network and settling in child rights - Burgos, Marcelo Baumann (Tempo Social, 2020)
The Statute of the Child and Adolescent, approved in 1990, installs in the country a radically new model of education for children. Among these novelties, is the idea that the right of the child should be disseminated and administered by a set of actors who work in the network. Based on an empirical research on some of these actors, this article describes how child rights have been shared, and how a polysemic notion of the network informs their practices. More specifically, it seeks to how schools, guardianship councils, prosecution in childhood and adolescence, and public centers in social assistance deal with the right to a child and how deal with its operationalization in a network.